2006
DOI: 10.1111/j.1478-3231.2006.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of magnetic resonance imaging flowmetry of portal and hepatic veins in patients following hepatectomy

Abstract: Our results suggest that MRI flowmetry is a potentially useful tool for measurement of hepatic blood flow and recommend its use for estimation of liver cirrhosis-associated impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…We therefore speculate that the differences in MR imaging and US flow measurements are mostly related to partial volume effects. Concordant with our findings, investigators in earlier studies report larger portal vein areas when assessed with MR imaging compared with Doppler US (15,35). A potential source of dissenting results between MR imaging and Doppler US measurements of portal vein area size may be measurement site differences, representing a limitation of our study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We therefore speculate that the differences in MR imaging and US flow measurements are mostly related to partial volume effects. Concordant with our findings, investigators in earlier studies report larger portal vein areas when assessed with MR imaging compared with Doppler US (15,35). A potential source of dissenting results between MR imaging and Doppler US measurements of portal vein area size may be measurement site differences, representing a limitation of our study.…”
Section: Discussionsupporting
confidence: 89%
“…In their study, Gaiani et al (45) described an overall prevalence of 4D MR imaging underestimations of 31%-39% compared with US measurements of blood-flow velocities in the carotid bifurcation. Nanashima et al (35) observed that underestimation of mean flow velocities in the portal vein by 19.2% occurred with MR imaging compared with Doppler US. The maximum (22.7 cm/sec 6 7.1) and mean (9.6 cm/ sec 6 3.1) velocities of MR imaging in our study were slightly lower than those in previous MR studies (ie, Yzet et al [16], with a maximum velocity of 28.2 cm/sec 6 8.8; Lycklama à Nijeholt et al [15] and Nanashima et al [35], with a mean velocity of 10.8 cm/sec 6 1.6 to 13.5 cm/sec 6 3.7).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This procedure is associated with hemodynamic and oxygen metabolism disturbances of the residual liver that may lead to post-operative complications and liver failure [1][2][3]. In a normal liver, postoperative dysfunction may be transient and it is usually associated with intensive regeneration which depends on the supply of energy [4,5].…”
Section: Introductionmentioning
confidence: 99%